Deterrent Measures of Tax Fraud on Tax Compliance in Nigeria - Umanhonlen Felix Ogbeiyulu (2022) (The Certified National Accountant, A Quarterly Journal of the Association of National Accountants of Nigeria (ANAN), 2022)
Government all over the world generates revenue for expenditure through tax. Tax compliance gives incentive to tax control and reduces collection burden. However, this paper focused on deterrent measure of tax fraud on tax compliance in Nigeria. Specifically, the paper examined the influence of stiff penalty, tax audit, tax amnesty and tax deterrence policy on tax compliance. This study is an expost facto and field survey research type, which employed combination of both qualitative and quantitative design covering time frame of five years from 2016 to 2020. The main instrument used in the study was questionnaire administration and analyzed with least square regression method. The study revealed that stiff penalty, tax audit and tax deterrence policy indicated positive significant relationship with tax compliance, and by implications were critical influencing deterrent tax fraud measures enhancing tax compliance. The study also showed that tax amnesty has no significant influence but positively related with tax compliance which by implication is a weak enhancing factor of tax compliance. It is therefore recommended that tax authorities in federal and states should ensure that stringent penalty and policies are melted on defaults taxpayer as to enhance compliance to boost revenue for government expenditure.
The Certified National Accountant Journal and Deterrent tax fraud and tax related issues
Keywords: Deterrent Policy; Tax Fraud; Stiff Penalty; Tax Compliance; Tax Audit; Tax Amnesty; Fines